Good practices and inclusive Art at the University: the image of the Artist/Teacher and Innovative Pedagogies - Navajas Seco, Rosaura (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2016)
The aim of art, as transformer of the individual, has numerous sides which give the human beings a sense of enhancement and growth. It is considered by university the need for our students to take part of this process of social transformation in which they feel the need of helping the community when its members are at risk of social exclusion. Art is considered to be a means, a tool and a purpose for an artis-pedagogue to be used as a guide for the renewal. And the university is also considered as a focus of commitment by means of the development of good practices as well as adopting an open and innovative attitude to any changes aimed at living harmoniously within a more just society.